STUDI TENTANG PEMBENTUKAN KEBIASAAN DAN PERILAKU SOSIAL SISWA (STUDI KASUS DI SDN 1 WINDUJANTEN) - Nunu Nurfirdaus; Risnawati Risnawati (Jurnal Lensa Pendas, 2019)
The purpose of this study was to find out about the social habits and behavior of Windujanten 1 Elementary School students. The method used in this study is descriptive qualitative with the method of determining resource persons using purposive sampling technique. The main resource persons in this study were 3 class IV students, 3 grade V students, 3 grade VI students, 5 teachers and the principal of Windujanten Elementary School 1. Data collection techniques are observation, interview and documentation. The results showed that the formation of habits and social behavior of students in the school environment was very good. This is supported by the habits and values ​​applied by the teacher to students. The recommendations that can be given regarding this research are that the collaboration between parents of students and the school is more intense in terms of applying good habits in forming and applying good values ​​to students. Because after all the collaboration between the school and parents of students is needed in educating students.